A Work study on Standard Products Exporters, Inc. - Fernandez, Joy Khristina; Gopalan, Leslie; Laureta, Candice (Diliman, Quezon City College of Engineering, 1993)
With the conclusion of the Time and Motion Study, the group proposes the following changes be implemented to improve overall efficiency of the systems studied : 1. the use of trolleys for materials handling; 2. availability of tools and materials on demand; 3. frequent meetings between executives; 4. the implementation of a wage incentive scheme; 5. furniture and tools of appropriate design be issued; 6. adequate lighting and ventilation; 7. educate/inform workers on their contributions to the job order; 8. existing forms should be filled in completely; 9. construction of a materials warehouse; 10. implementation of new facilities/site layout. Please read the relevant section(s) for further information and/or suggested layouts/design ideas.
Feasibility study
Keywords: Standard Products Exporters Incorporated; Systems analysis